Avaliação do potencial fitorremediador da mamona (Ricinus communis L.) e girassol (Helianthus annuus L.) quanto à remoção de chumbo e tolueno em efluentes sintéticos. - Lima, Anita Maria de (2010)
The development of research that aim to reduce or even eliminate the environmental impacts provided by anthropogenic actions. One of these main action is the discard of industrial waste in the biotic compartments such as soil, water and air, gained more space in academic settings and in private. A technique of phytoremediation involving the use of plants (trees, shrubs, creepers and aquatic) and their associated microorganisms in order to remove, degrade or isolate toxic substances to the environment. This study aimed to evaluate the potential for phytoremediation of castor bean (Ricinus communis L.) and sunflower (Helianthus annuus L.), wild crops suitable region of Rio Grande do Norte, to reduce concentrations of lead and toluene present in synthetic wastewater that simulate the characteristics of treated water production originated in the petrochemical Guamaré. The experiment was accomplished in randomized blocks in four replicates. Seeds of BRS Energy for the development of seedlings of castor beans and sunflower for Catissol 01, both provided by EMPARN (Empresa de Pesquisa Agropecuária do Rio Grande do Norte) were used. Lead concentrations tested were 250, 500 and 1000 mg/L called T2, T3 and T4, respectively, for toluene the concentrations used were 125, 256 and 501 μg/L, called T5, T6 and T7, respectively. The data for removal of lead in relation to sewage systems applied in castor bean and sunflower were 43.89 and 51.85% (T2), 73.60 and 73.74% (T3) and 85.66 and 87.80 % (T4), respectively, and toluene were approximately 52.12 and 25.54% (T5), 55.10 and 58.05% (T6) and 79.77 and 74.76% (T7) for castor and sunflower seeds, respectively. From the data obtained, it can be deduce that mechanisms involved in reducing the contaminants were of phytoextraction, in relation to lead and phytodegradation for toluene. However, it can be concluded that the castor bean and sunflower crops can be used in exhaust after-treatment of industrial effluents that have this type of contaminant